Identifikasi dan Strategi Pengembangan Potensi Desa Wisata Alternatif di Desa Pringkasap Kecamatan Pabuaran Kabupaten Subang - Farida Farida; Lidia Djuhardi; Nana Trisnawati; Estu Mahanani; Marhalinda Marhalinda; Endang Ayu Rahayu (Universitas Persada Indonesia YAI, 2023)
This study aims to identify the potential of alternative tourism villages and the external andinternal factors that are owned in Pringkasap Village, Pabuaran District, Subang Regency. Thistype of research is qualitative, with the method of collecting data through FGD. The analytical toolused is a SWOT (strength, weakness, opportunity and threat) analysis, which aims to determine analternative tourism village development strategy. The results of the study resulted in severalstrategic directions for the development of tourist villages, including competitive strategies,overview strategies, diversification strategies and defensive strategies